A thymic stromal lymphopoietin polymorphism may provide protection from asthma by altering gene expression. Issue 4 (14th February 2020) - Moorehead, Amy; Hanna, Raphael; Heroux, Delia; Neighbour, Helen; Sandford, Andrew; Gauvreau, Gail M.; Sommer, Doron D.; Denburg, Judah A.; Akhabir, Loubna
Abstract: Background: Genome‐wide association studies have identified associations of the single nucleotide polymorphism rs1837253 in the thymic stromal lymphopoietin ( TSLP ) gene with asthma, allergic disease and eosinophilia. The TSLP gene encodes two isoforms, long and short, and previous studies have indicated functional differences between these two isoforms. Objective: We investigated the expression of these TSLP isoforms in response to a pro‐inflammatory signal, and the role of the rs1837253 genotype in gene isoform regulation. Methods: We cultured nasal epithelial cells of asthmatic and non‐asthmatic subjects and evaluated poly(I:C)‐induced TSLP protein secretion using multiplex protein assays and gene expression profiles of the TSLP isoforms, and related genes using real‐time qPCR. We correlated these profiles with rs1837253 genotype. Results: Asthmatic nasal epithelial cells exhibited increased TSLP protein secretion compared with nasal epithelial cells from healthy controls. The long TSLP isoform was more responsive to poly(I:C) stimulation. Additionally, the minor T allele of rs1837253 was less inducible than the major C allele, suggesting differential regulation; this may explain the "protective" effects of the T allele in asthma. Conclusion: Our results provide important insights into the differential regulation and function of TSLP isoforms, including the role of TSLP rs1837253 polymorphisms in allergic inflammatory processes. Clinical relevance: The key finding on the influence of TSLP genetic variation on disease expression/endotype could provide basis for investigation into targeted biologics for anti‐TSLP therapies.